2007
DOI: 10.1111/j.1468-0092.2007.00287.x
|View full text |Cite
|
Sign up to set email alerts
|

An Anglo‐saxon Execution Cemetery at Walkington Wold, Yorkshire

Abstract: This paper offers a new perspective on a previously insecurely dated Anglo-Saxon cemetery at Walkington Wold in east Yorkshire (Fig. 1). The results of excavations at the site were published in 1973, but more recent examination of the skeletal material, including the acquisition of radiocarbon dates, casts new light on the cemetery and its significance. Rather than being of late Roman or early post-Roman date, as has been previously suggested, it can now be demonstrated that the cemetery includes a series of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 12 publications
1
14
0
Order By: Relevance
“…Second, these burial containers tend to appear in graves where other uncommon objects appear. This pattern has been noted not only in the present study, but in various studies concerning the entire Anglo‐Saxon period (Hirst 1985, 32–3; Buckberry 2004). During the seventh–eleventh century in northern England the majority of interments were plain earth‐dug graves (Buckberry 2007, 118; Craig 2010, 132), and therefore it seems viable to consider that an elaboration such as a chest would have been utilized as a higher‐status rite.…”
Section: Chest Burials and Social Statussupporting
confidence: 87%
“…Second, these burial containers tend to appear in graves where other uncommon objects appear. This pattern has been noted not only in the present study, but in various studies concerning the entire Anglo‐Saxon period (Hirst 1985, 32–3; Buckberry 2004). During the seventh–eleventh century in northern England the majority of interments were plain earth‐dug graves (Buckberry 2007, 118; Craig 2010, 132), and therefore it seems viable to consider that an elaboration such as a chest would have been utilized as a higher‐status rite.…”
Section: Chest Burials and Social Statussupporting
confidence: 87%
“…It has been abundantly demonstrated that in many societies, some individuals underwent funeral treatment that differed from the usual burial practice (Binford, ). These differences, identifiable at the archaeological level, may be symptomatic of motivations connected to religious beliefs and the magical sphere, such as belief in vampires and revenants (Cornelio‐Cassai & Cavallari, ; Redi, Forgione, Savini, & Amoretti, ), or may be an expression of the marginal role played by some individuals within the social order of the community, as would be the case for outlaws (Buckberry, ). According to this shared assumption, our burial represents a funerary custom that clearly falls within the category of so‐called deviant or atypical burials, which are often interpreted as indicative of social marginality and deviancy (Murphy, ; Reynolds, ).…”
Section: Resultsmentioning
confidence: 99%
“…First, that all of the published osteological examples of impaired individuals who have received nonnormative burial are adult males. Adult males also comprise most of all kinds of deviant burial from the Anglo‐Saxon period (Buckberry & Hadley, : 311, 315–6; Reynolds, : 155–6). It is unclear whether it would have been considered appropriate to afford women or children deviant funerary rites in any context, whether motivated by criminal behaviour, physical incapacity or mental illness, and therefore whether we should expect disability to be reflected in deviant burial of women or children.…”
Section: Resultsmentioning
confidence: 99%